2008
DOI: 10.1128/jb.01538-07
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Imaging of the Highly Bent Architecture of Bdellovibrio bacteriovorus by Using Cryo-Electron Tomography

Abstract: Bdellovibrio bacteriovorus cells are small deltaproteobacterial cells that feed on other gram-negative bacteria, including human pathogens. Using cryo-electron tomography, we demonstrated that B. bacteriovorus cells are capable of substantial flexibility and local deformation of the outer and inner membranes without loss of cell integrity. These shape changes can occur in less than 2 min, and analysis of the internal architecture of highly bent cells showed that the overall distribution of molecular machines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
51
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 40 publications
10
51
0
Order By: Relevance
“…3F). This is in contrast to the centrally located nucleoid and peripherally located ribosomes observed in many other bacterial species (18,19,32). Three-dimensional modeling of nucleoids and ribosome-like particles indicated that these subcellular structures were compartmentalized into two distinct zones, each taking up roughly one-half of the volume enclosed by the IM (Fig.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…3F). This is in contrast to the centrally located nucleoid and peripherally located ribosomes observed in many other bacterial species (18,19,32). Three-dimensional modeling of nucleoids and ribosome-like particles indicated that these subcellular structures were compartmentalized into two distinct zones, each taking up roughly one-half of the volume enclosed by the IM (Fig.…”
mentioning
confidence: 78%
“…In addition, rapid freezing (which occurs within ϳ1 ms) preserves the cells in a nearly native state without chemical fixation or staining, which allows accurate measurement and examination of the cell dimensions and internal structures. In the past few years, cryo-ET has yielded great insights into the internal organization of many commonly studied Gramnegative bacteria (18)(19)(20), archaebacteria (21), cyanobacteria (22), mycobacteria and mycoplasmae (23), viruses (24,25), and bacterial phages (26) and, more recently, the cellular architecture of eukaryotes (27,28).…”
mentioning
confidence: 99%
“…1), strongly suggesting that it does not stem from physical constraints in the bdelloplast but rather results from a regulated cell plan. A recent study has shown that the Bdellovibrio cell is unusually flexible and contains numerous filamentous structures (8). Notably, MreB, an actin-like homolog, is present as two copies in B. bacteriovorus.…”
Section: Discussionmentioning
confidence: 99%
“…The host-dependent B. bacteriovorus strains used in this study were the following: wild-type predatory HD100; HD100mreB2-mtfp, a strain containing integrated plasmid pAKF40a, a kanamycin resistance gene replacement vector that replaces wild-type mreB2 with an mreB2 that is fused in frame at its C terminus with the coding sequence of monomeric bright teal fluorescent protein, mTFP; and the control strain HD100Bd2345::Km r , a cell line that has an integrated pK18mobsacB kanamycin resistance vector to disrupt the ABC transporter gene to act as a plasmid control for the pK18 backbone of pAKF40a (17). HD100 was cocultured at 22 to 25°C with E. coli strain RP3098, a mutant with all flagellar and chemotaxis proteins deleted and grown as described previously (3). The other two strains were cocultured at 29°C on YPSC (yeast extract, peptone, sodium acetate, and Lcysteine) overlay plates with E. coli strain S17-1 that contains plasmid pZMR100 to confer kanamycin resistance (17).…”
Section: Methodsmentioning
confidence: 99%